Legal Review of the Requirements Become a Candidate for DPRD Member Who Graduate from Senior High School That’s Still Pro and Contra - Agustiawan Saragih; Abdillah Abdillah; Ismayani Ismayani (IHSA Institute, 2023)
DPRD is a Regional People's Representative Body as a representation of the people, has the function of Forming Regional Regulations, Budgeting and Oversight which of course requires people who are experts in their fields. The aim of the research is to conduct a legal review regarding the requirements for prospective DPRD members who graduate from high school who still have pros and cons. The type of research in this paper is normative with a statutory and conceptual approach. While the specification of the research is analytical descriptive, namely explaining the problem according to the research title. The data used is secondary data which consists of primary legal materials in the form of Law No. 7 of 2017, Law No.23 of 2014 and related laws in research journals and secondary legal materials in the form of books, journals, electronic news, laws and regulations, opinions of legal experts and writings related to research title. The legal review regarding the requirements for prospective DPRD members to graduate from high school does fulfill one of the requirements in the laws and regulations, but to become a people's representative or legislator with a high school diploma equivalent can be said to be not yet an expert or broad-minded due to limited education. Therefore, it is suggested that the requirements for candidates for legislative members need to increase the standardization of minimum education for candidates for legislative members who have graduated from university, at least a Bachelor of Laws or Bachelor degree related to executive, legislative and judicial policies.